Development of A Physical Rehabilitation Therapy Model for Pain Plantar Fascitis Using Ultrasound and Theraband Exercise Methods - Muchlis, Arif Fadli; Fajri, Hadi Feri; Silviani, Iit (Indonesian Journal of Sport Management, 2025)
The aim of this research is to develop a special physical rehabilitation therapy model to treat pain due to plantar fasciitis. In this context, this research or study focuses on two main methods, namely the use of ultrasound and theraband exercise, as approaches to reduce pain and improve foot function. Plantar fasciitis is inflammation or degeneration of the plantar fascia, which is the thick connective tissue that runs along the sole of the foot from the heel to the toes. This condition occurs due to repeated pressure or injury that causes micro-tears in the fascia, which then triggers pain and inflammation. To overcome the problem of pain in cases of plantar fascitis, researchers want to develop physical rehabilitation therapy using Ultrasound and providing a strengthening exercise program using theraband exercise media. The development of physical rehabilitation therapy emphasizes determining the ultrasound wavelength along with the theraband exercise dose. In accordance with the type of research that will be carried out, namely research on the development of rehabilitation therapy models, the research procedure that will be carried out is a research and development research procedure. The steps that will be carried out are as follows: (1) exploring potential and problems, (2) data collection, product design, (4) design validation, (5) design revision, (6) product trials, (7) product revisions, (8) use trials, (9) product revisions, and (10) mass production. From the research results which are in accordance with the steps that will be carried out in this research, the Ultrasound and Theraband Exercise Method can reduce pain in the condition of Plantar Fascitis.